Effects of clinicopathological factors on prognosis of young patients with resected breast cancer. Issue 5 (5th February 2021) - Li, Wen; Deng, Yunfu; Wu, Qiang; Chen, Wenjie; Liu, Zhengkun; Wang, Ting; Ai, Cheng; Chen, Fang; Wang, Zhu; Ma, Guangzhi; Zhou, Qinghua
Abstract : Abstract: This study aims to analyze the relationship between clinicopathological characteristics and survival in young patients (⩽35 years old) with resected breast cancer. A total of 173 cases were included in this study. The clinicopathological factors potentially associated with prognosis were evaluated. Furthermore, we categorized patients into different groups to evaluate the prognosis according to hormone receptor status or important risk factors. Younger age (⩽30 years) was an independent predictor for poor disease-free survival (DFS) and overall survival (OS). Besides, PR negative status, tumor grade, and advanced lymph nodes postsurgery were independent prognostic factors of DFS, while PR negative status and advanced lymph nodes postsurgery were independent prognostic factors of OS. For hormone receptor-positive patients, people with ER+ or PR+ and HER2−/+ showed poorer prognosis than the other 2 levels. Risk factor grouping based on the ER, PR, HER2, Ki-67 status, tumor grade, and lymph nodes postsurgery showed that patients in highest score group received the poorest prognosis. Grading system based on the hormone status or the risk factor grouping may offer a useful approach to assess which subgroups of young breast cancer present poorer prognosis.